La Hoja from Medellin and its influence on the local journalism and the exercise of citizenship - Forero Arango, Ximena (Folios, revista de la Facultad de Comunicaciones y Filología, 2016)
The agenda of the city, the inclusion of profiles of illustrious citizens worthy of emulation, and the use of the ethos as a rhetorical proof, on the basis of the Argumentation Theory, did that the magazine La Hoja de Medellín is becoming, at the end of the Twentieth Century and at the beginning of the Twenty-first Century, into the framework of the conception of the communication media, as transformers of the social reality, in a critical historical moment for the city, marked by the effect of the drug trafficking crisis.